Ecology of Etiquette as a Factor in the Formation of a Harmonious Educational Environment at School (Journal of Educational Sciences, 2026)
The ecology of etiquette in the school environment is considered a multidimensional system that includes value guidelines, communicative standards, and culturally determined behavior patterns of participants of the educational process. The introduction of etiquette practices into the structure of school life contributes to the harmonization of the educational environment, strengthens the emotional stability of students, and reduces the level of interpersonal conflict. An ecological approach allows interpreting etiquette as a holistic environment that regulates the quality of interaction and the moral and psychological climate of the school. It is shown that the development of etiquette reduces communication barriers, increases the effectiveness of pedagogical communication, and promotes the formation of a cooperative culture. Such an environment stimulates constructive dialogue, develops empathy, and creates conditions for the holistic personal development of students. This article examines the ecology of etiquette as a significant factor in the formation of a harmonious educational environment, associated with an ecocentric type of consciousness and a focus on the natural mechanisms of personal development. Etiquette practices are analyzed through three structural aspects – communicative-verbal, emotional-psychological, and ethical-behavioral – reflecting the mutual influence of teacher and student. To verify the theoretical positions, methods of analyzing scientific literature, normative sources and modern publications, as well as empirical survey of teachers and students were used. The sample consisted of 120 teachers and 120 students in grades 7–11 from Astana, Almaty, and Shymkent. The data obtained show that ecological etiquette enhances communication quality and promotes psychological well-being, however, some students report emotional stress, indicating the need to develop empathy and emotional resilience in teachers. The results confirm the connection between teacher communicative culture, emotional climate, and the ethical resilience of educational relationships.Keywords : etiquette ecology, school environment, educational harmony, ethical communication, pedagogical interaction, emotional well-being, social cohesion.